Mortality among World Trade Center rescue and recovery workers, 2002–2011. Issue 2 (4th January 2016) - Stein, Cheryl R.; Wallenstein, Sylvan; Shapiro, Moshe; Hashim, Dana; Moline, Jacqueline M.; Udasin, Iris; Crane, Michael A.; Luft, Benjamin J.; Lucchini, Roberto G.; Holden, William L.
Abstract : Background: Rescue and recovery workers responding to the 2001 collapse of the World Trade Center (WTC) sustained exposures to toxic chemicals and have elevated rates of multiple morbidities. Methods: Using data from the World Trade Center Health Program and the National Death Index for 2002–2011, we examined standardized mortality ratios (SMR) and proportional cancer mortality ratios (PCMR) with indirect standardization for age, sex, race, and calendar year to the U.S. general population, as well as associations between WTC‐related environmental exposures and all‐cause mortality. Results: We identified 330 deaths among 28, 918 responders (SMR 0.43, 95%CI 0.39–0.48). No cause‐specific SMRs were meaningfully elevated. PCMRs were elevated for neoplasms of lymphatic and hematopoietic tissue (PCMR 1.76, 95%CI 1.06–2.75). Mortality hazard ratios showed no linear trend with exposure. Conclusions: Consistent with a healthy worker effect, all‐cause mortality among responders was not elevated. There was no clear association between intensity and duration of exposure and mortality. Surveillance is needed to monitor the proportionally higher cancer mortality attributed to lymphatic/hematopoietic neoplasms. Am. J. Ind. Med. 59:87–95, 2016. © 2016 Wiley Periodicals, Inc.